Avaliação sensorial, composição proximal e de ácidos graxos do leite, sorvete e queijo mussarela de vacas mestiças suplementadas com óleo de palma ou de coco - Corradini, Silvana Aparecida da Silva (2013)
Milk is considered the most nutritionally complete beverage for human consumption. Children of all ages, the elderly, and the convalescent are groups which need considerable amount of milk in their diet. Milk exceptional nutrition value is a result of its constituents such as proteins, carbohydrates, fats, minerals, and water. Nowadays, there is not only natural milk but also a diverse range of milk sub products which are manufactured and consumed in large scale worldwide. Among milk sub products, cheese and ice cream are the most widely consumed. By definition, cheese can be either a fresh or an aged product resultant of milk coagulation with subsequent processing necessary to give each kind of cheese its characteristics and flavors. The coagulation process during cheese production may occur by means of physical action of rennet or other kinds of coagulants, with partial separation of whey. Mozzarella cheese accounts for the highest amount of production in Brazil. Estimates indicate that mozzarella cheese production will exceed 200 million tons (FILHO, 2010). The overall augmentation of population income contributes to increasing cheese consumption. Cheese is no longer considered a product exclusively for elite consumption and can be included on a daily basis in the diet of everyone. In addition, cheese is widely utilized in fast food processing, given its properties such as slicing possibility and melting, which are essential to food attractiveness and flavor. Ice cream belongs to the category of edible frozen food. Ice cream is obtained from an emulsion of fats and proteins, with or without addition of other ingredients and substances submitted to freezing, under conditions that guarantee the product conservation in its frozen or partially frozen state during storage, transportation, and delivery (ANVISA, 2005). Breakthroughs in the dairy sector during the last few years are responsible for the diversity and quality of dairy food products available nowadays. That was a result of the kind of nourishment given to cattle, rich in fatty acids. These fats are essential for the functioning of the human body. Are essential nutrients, ie there is no endogenous production, as well must be present in the diet. In this context, this work contributes to efficiency improvement in the milk production chain by means of finding nutritional strategies to increase the quality of the milk, the primary product, emphasizing mainly factors related to fat content, and later applying the primary product to make dairy foods (cheese, mozzarella, and ice cream). The first phase of the project happened in Marques Farm, located in the city of Mirador-PR. Three treatments were applied with 23 healthy animals, in the same stage of lactation in December, 2010 i.e., a rainy season. The feeding treatments were: control group, palm oil, and coconut fat. The first gathering of milk occurred 21 days after the diet change and the second after 36 days. Milk physicochemical analysis (humidity, protein, fat, ashes, lactose, total dry extract, and acidity) was performed utilizing the Ekomilk ultrasonic analyzer. Milk samples were taken to a laboratory called Clinica do Leite, located in Piracicaba-SP where bacteria counting (CBT) and somatic cells counting (SCC) were determined. From the obtained milk, many samples of mozzarella cheese and ice cream were prepared and analyzed in the university laboratory. Several evaluations were performed in this laboratory, including determination of centesimal composition such as humidity and ashes (IAL, 2005), fat content (Bligh & Dyer, 1959), protein (AOAC, 1995), carbohydrates by difference, and pH.A physicochemical analysis was conducted after manufacturing of the dairy products and were performed in triplicate. 10 Samples of both cheese and ice cream utilized in the sensorial analysis were microbiologically tested to verify if thermo tolerant Coliforms, Staphylococcus positive coagulase, or Salmonella were present. Microbiological analyses were performed according to the methodology recommended by MAPA (2003). Samples of ice cream and cheese were given in an alternated manner as a strategy to prevent taster fatigue, considering the high number of samples given to each taster. Fifty untrained tasters proved the two products separately. Sensorial analysis utilized hedonic scale of nine points for aroma, flavor, color, and texture. This process was approved by the UEM's ethics committee with number 703/2011 and CAAE: 0415.0.093.000-11. Tasters received the samples in containers randomly numbered and were instructed to clean their palate by drinking water in the period between tasting different samples. Color was evaluated by means of the portable colorimeter Minolta® CR10, with integration sphere and vision angle of 3º, i.e., d/3 illumination and D65 illuminant. The system utilized was the CIEL a*b*. Texture analysis was performed in a Stable Micro Systems Texture Analyzer TAXT2 (Texture Technologies Corp, England) utilizing a HDP/WBV probe when testing cheese and a P- 36mm probe for ice cream testing. Fatty acids chromatographic analysis for milk, ice cream, and cheese were performed in the Chemistry laboratory at UEM. The trace ultra 3300 chromatograph works with Thermo gas and is equipped with a flame ionization detector and a fused capillary column CP - 7420 (Select FAME, 100 m long, 0.25 mm inner diameter, and 0.25 μm of cuanopropyl). Melting and yield capabilities were studied in determining cheese characteristics, while the ice cream was evaluated for overrun. Data statistical analysis included variance analysis (ANOVA) and average calculation by Bonferroni with 5% significance level, evaluating the influence of feeding (three treatments: control, coconut, and palm) in the separated period. Milk's physicochemical analysis showed no significant changes in humidity, protein, fat, ashes, lactose, total dry extract, and acidity (P<0.05). Besides, they were found to be within the acceptable range according to values established by the code called Instruction Normative Nº62 (2011). All samples that presented differences in results of SCC and CBT's analysis were immediately disposed. Therefore, they were not employed in the subsequent phases of this project. Milk's fatty acid tests show a reduction of saturated fatty acids content during the two periods of milk gathering for both treatments (coconut and palm). In both gathering periods the presence of rumenic acid, also called linoleico conjugated acid (CLA, 18:2c9t11) was detected. Cheese and ice cream physicochemical analyses revealed no significant difference (P<0.05) incliding all tested parameters. Microbiological analyses proved that the three parameters examined were within limits established by legislation (RDC n12, ANVISA). Regarding sensorial analyses, all samples evaluation were rated in a range from liked moderately to liked a lot, showing a great acceptance from the tasters (acceptance index >=70%). Attributes such as aroma, color, and texture did not change significantly (P<0.05). Products prepared with milk obtained from cows fed with coconut oil received better scores regarding flavor (7.56) in comparison with 6.78, obtained for products prepared with milk obtained from cows fed with palm oil. Cheese sensorial analysis revealed no significant difference (P<0.05) regarding aroma, flavor, and color. Texture was better ranked for the witness and coconut treatment when compared to palm oil, similarly the same findings obtained for flavor in ice cream. Color for both cheese and ice cream were within acceptable range of values found in literature. Ice cream instrumental texture analysis and overrum showed no substantial difference for 11 the three samples in any of the periods evaluated. Cheese yield analysis revealed no significant change as well. However, cheese texture values were higher when derived from cows fed with coconut oil, with a 75.10 Kgfin time 1 and 64.55 Kgf in the time 2. In gas chromatographic analysis of ice cream for all treatments fatty acids has been highlighted that the palmitic acid (16:0), vaccenic (18:1 n-7), stearic (18:0), myristic (14:0) and lauric (12 : 0) respectively. Trans fatty acids identified were elaidic acid (18:1-9t) and CLA (C18: 2c9t11). Among saturated fatty acids found in cheese, a greater amount of palmitic acid (16:0), stearic acid (18:0), and myristic acid (14:0) were detected. Results show that the kind of cow feeding has influence on the quality of milk and its sub products. Therefore, increasing the source and variety of fat in cow feeding is a feasible strategy towards obtaining milk and milk sub products with a better quality